Oral administration of misoprostol reduces postpartum Haemorrhage in urban slums of Bangladesh - Banu, Morsheda; Nahar, Shamsun; Hashima-E-Nasreen (BRAC Research and Evaluation Division (RED), 2019)
To avert deaths from postpartum haemorrhage (PPH), Manoshi initiated community health workers (CHW) administered oral misoprostol (400~g) to women following childbirth either at delivery centers or home in slums of Dhaka and under Gazipur City Corporation in 2009. To study whether the supervised use of misoprostol would reduce primary PPH following childbirth including its feasibility and community acceptability. A non-randomized control trial was undertaken among 3,900 women in urban slums of Dhaka and Gazipur City Corporation during January-August 2011 . Oral misoprostol was prophylactically given to the treatment group following childbirth, while the control group did not receive it. The misoprostol significantly reduced incidence of primary PPH in the intervention group (4.5%) compared to the control group (7.5%). The median blood loss of PPH cases was 868 ml in the treatment and 928 ml in control group. It reduced the rate of bleeding-related emergency transfer, additional medical interventions compared to control group. However, no significant difference was found in blood transfusion between the two groups. We found one-third of the women were aware about misoprostol in intervention while none were aware in the control. The median risk for developing PPH was lesser in the intervention and prolonged third stage of labour found significantly higher in the control group. Misoprostol was found to be widely accepted in the community and feasible to offer parturient by CHWs within 5 minutes following childbirth in intervention group. Prophylactic use of misoprostol administered by CHWs is feasible and effective in reducing the incidence of primary PPH in the parturient of slums of Bangladesh. Besides, community-based education on misoprostol and iron intake throughout pregnancy to reduce the need for blood transfusion should be ensured.